Nondestructive testing, assessment, and strengthening for reducing the seismic vulnerability of masonry structures - Ferreira, Tiago Miguel (2021)
Over the last decades, various regions of the globe have been hit by devastating seismic events leading to raise the awareness of the scientific, technical, and political communities to the need of identifying the buildings at risk and implementing effective mitigation strategies. The capacity to accurately assess the seismic vulnerability of these buildings plays a fundamental role in this context, mainly because among the three factors that make up the standard formulation of risk (i.e., hazard, vulnerability, and exposure), vulnerability is the only factor in which engineering research can intervene. Nevertheless, and despite the significant advances in the fields of structural and seismic engineering, there is still much to be done, particularly in what regards to the assessment of existing masonry buildings, which is simultaneously one of the vulnerable and varied construction typologies. This chapter aims to contribute to bridging this gap by offering a comprehensive review of the most relevant nondestructive inspection and testing procedures, assessment approaches, and strengthening solutions to existing masonry buildings.